2016
DOI: 10.1590/2317-4889201620160078
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the geometry of diabase sills of the Serra Geral magmatism, by 2D seismic interpretation, in Guareí region, São Paulo, Paraná basin, Brazil

Abstract: ABSTRACT:The Paraná Basin holds in its stratigraphic record a thick layer of volcanic rocks related to the opening of the Gondwana Supercontinent, which occurred during the Eocretaceous. Based on the interpretation of three two-dimensional (2D) seismic lines in the region of Guareí, East-Central São Paulo state, in the Southeast of Brazil, the subsurface geometries of these volcanic rocks were identified. Since the original seismic resolution quality was low, alternative techniques were utilized to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…On the other hand, for shale gas and shale oil exploration, the best areas to be prospect would be where Irati Formation is close to intrusive rocks as described by several authors (e.g. Milani and Zalán, 1999;Araújo et al, 2000;Correa and Pereira, 2005;Costa et al, 2016 The mineralogical content of the Assistência Member presents intervals rich in quartz, plagioclase, carbonates and clay minerals. These major constituents often occur in areas where shale gas and shale oil are explored around the world.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, for shale gas and shale oil exploration, the best areas to be prospect would be where Irati Formation is close to intrusive rocks as described by several authors (e.g. Milani and Zalán, 1999;Araújo et al, 2000;Correa and Pereira, 2005;Costa et al, 2016 The mineralogical content of the Assistência Member presents intervals rich in quartz, plagioclase, carbonates and clay minerals. These major constituents often occur in areas where shale gas and shale oil are explored around the world.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors (e.g. Milani and Zalán,1999;Araújo et al, 2000;Correa and Pereira, 2005;Costa et al, 2016) emphasized the role of the heat effect deriving from the diabase sills in the maturation of organic matter present in the shales.…”
Section: Study Area: Geologic Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Assistência Member, a shallow marine environment under basin restriction (low circulation and oxygenation), which allowed the deposition of black carbonatic shales, which developed on shelf areas (Araújo et al, 2000). Costa et al (2016) demonstrated, through 2D seismic interpretation, that the Irati Formation contains post-Triassic, basic igneous bodies, composed of dykes and sill with thicknesses that vary in different parts of the basin. In the study area, the isopach map of Serra Geral Formation shows the occurrence of thick intervals of igneous rocks in contact with Irati Formation (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…Irati levam a essa formação ser considerada um sistema petrolífero atípico (Araújo et al, 2000). A interação ígnea-sedimentar pode ser mapeada em sísmica (Costa et al, 2016) ou observada diretamente em pedreiras, por exemplo, na borda Leste (Holanda et al, 2020;Martins et al, 2020) e na parte Norte da Bacia do Paraná, em Goiás (por exemplo Oishi, 2017;Oishi et al, 2019;Mabecua et al, 2020). Nessa região, a observação de feições ígneas complexas (Figura-02) similares as feições tipo dedo ("fingers") já descritas na Bacia de Neuquén (Galland et al, 2019), evidencia que, sob a perspectiva exploratória, o entendimento da geometria dos corpos ígneos é vital para a compreensão dos processos de maturação e geração de hidrocarbonetos.…”
Section: Formação Irati E As Rochas íGneas Cretáceasunclassified